Document management system for enhancing efficiency in the logging industry - Khudyakova Elena; Tynchenko Vadim; Glinscaya Anna; Kukartseva Svetlana; Vodyannikov Vladimir (BIO Web of Conferences)
AIS EDiSZ includes electronic document management, an electronic map and an electronic schedule, which reduces equipment downtime, improves navigation and simplifies the receipt of tasks by employees. The introduction of AIS EDiSZ not only solves current problems, but also creates the basis for further digitalization of the industry, increasing the efficiency of enterprises and opening up opportunities for the introduction of innovative technologies. The study concludes with the design of the implementation of the system in the enterprise. The result of the work is the introduction of an automated information system for electronic document management and communication (AIS EDiSZ) to solve the problems of logging enterprises associated with unreliable document management and employee navigation.